Vaginal Preparation with Povidone Iodine and Postcesarean Infectious Morbidity: A Retrospective Trial - Yavuz, Esra Turgut; Malatyalıoğlu, Erdal; Bıldırcın, Fatma Devran (Gynecology Obstetrics & Reproductive Medicine, 2014)
OBJECTIVE: The aim of the study was to evaluate the effect of preventing development of postpartum infections by vaginal preparation with povidone iodine before cesarean delivery, with a retrospective file scanning. STUDY DESIGN: This study included 250 pregnant women undergoing cesarean delivery, who applied our clinic between the dates 2010-2011. All women received the standard antibiotic prophylaxis, 1 gr cefazolin iv before 30 minutes from the operation. Patients were investigated in two groups, vaginal cleansing with povidone iodine before cesarean delivery (126 case) or no cleansing (124 case), the groups compared with presence of postoperative fever endometritis and wound infection. RESULTS: Demographic characteristics of two groups were similar. There were no differences in age, height, weight, BMI, time of pregnancy, number of prior cesarean delivery, preoperative-postoperative time of staying in hospital, preoperative - postoperative hemoglobin values (p>0.05); there was only statistically significant difference in operating time (p<0.05). Analyzing the distribution of postoperative fever, there was only one case in vaginal cleansing group and four cases in the other group. There was no statistically significant difference between the groups (p>0.05). Comparing the two groups with postoperative wound infection, there is only one case in vaginal cleansing group and three cases in the other group. There is no statistically significant difference between the groups (p>0.05). Because of absence of endometritis in two, groups, we could not assess efficiency of vaginal cleansing in postpartum endometritis. No statistically significant difference was determined between the groups, in postoperative fever and postoperative wound infection (p>0.05). CONCLUSIONS: Vaginal cleansing with povidone iodine before cesarean delivery may decrease postoperative fever and wound infection morbidities, although this is not statistically significant.